2021
DOI: 10.3390/pharmaceutics13111877
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Internalization of Etoposide Using Dendrimer Nanospheres Loaded with Etoposide and Protoporphyrin IX on a Glioblastoma Cell Line

Abstract: Glioblastoma multiforme (GBM) is the most common malignant primary neoplasm of the adult central nervous system originating from glial cells. The prognosis of those affected by GBM has remained poor despite advances in surgery, chemotherapy, and radiotherapy. Photochemical internalization (PCI) is a release mechanism of endocytosed therapeutics into the cytoplasm, which relies on the membrane disruptive effect of light-activated photosensitizers. In this study, phototherapy by PCI was performed on a human GBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Among these co-treatments, the combination of PDT with chemotherapy is promising because of the high potential to eradicate cancer cells [ 136 , 137 , 138 , 139 ]. As reported, PDT treatment can affect the cell membrane permeability, and adding it as an adjuvant to chemotherapy may increase the deliverability of cytotoxic drugs [ 140 , 141 , 142 ]. Many studies have demonstrated that chemo-/photodynamic combination therapy can give excellent antitumor performances with the use of relatively low drug doses, even towards chemo-resistant cancers, and simultaneously overcome the limitations of PDT.…”
Section: Chemo-/photodynamic Combination Therapymentioning
confidence: 99%
“…Among these co-treatments, the combination of PDT with chemotherapy is promising because of the high potential to eradicate cancer cells [ 136 , 137 , 138 , 139 ]. As reported, PDT treatment can affect the cell membrane permeability, and adding it as an adjuvant to chemotherapy may increase the deliverability of cytotoxic drugs [ 140 , 141 , 142 ]. Many studies have demonstrated that chemo-/photodynamic combination therapy can give excellent antitumor performances with the use of relatively low drug doses, even towards chemo-resistant cancers, and simultaneously overcome the limitations of PDT.…”
Section: Chemo-/photodynamic Combination Therapymentioning
confidence: 99%
“…The study employed etoposide (Etop) and protoporphyrin IX (PpIX) loaded into polyamidoamine dendrimers nanospheres. This formulation showed enhanced cellular uptake compared to free PpIX, and light irradiation resulted in increased synergistic effects, oxidative stress, and apoptosis compared to treatment with Etop and PpIX alone [ 4 ].…”
mentioning
confidence: 99%